Technical report: solving a brain tumor growth equation by applying Adomian Decomposition Method / Alyaa Alway, Nadila Mohamad and Zamzuziliana Ismail @ Abdullah - Alway, Alyaa; Mohamad, Nadila; Ismail @ Abdullah, Zamzuziliana (2017)
In this project, the mathematical model of brain tumor growth introduced by a nonlinear partial differential equation. Since Adomian Decomposition Method (ADM) is a powerful technique to solve nonlinear partial differential equation, therefore, this project applies (ADM) into account the effects of combined use of radiotherapy and chemotherapy treatment. By computing the Adomian polynomials and substituting them into the mathematical model, this project finally get a solution of radius of the treated tumor. The solution obtained will be shown analytically by table a graph in the results and discussion section.